2011
DOI: 10.1038/ejcn.2011.77
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and vegetable intake influences the association between exposure to polycyclic aromatic hydrocarbons and a marker of oxidative stress in pregnant women

Abstract: Background/Objectives: Exposure to polycyclic aromatic hydrocarbons (PAHs) during pregnancy is known to increase oxidative stress, which may influence pregnancy outcomes and health of the child. Subjects/Methods: This study investigated whether fruit and vegetable intake modifies the relationship between exposure to PAHs and oxidative stress status during pregnancy. Urinary levels of 2-naphthol and 1-hydroxypyrene (biomarkers of exposure to PAHs), and malondialdehyde (MDA; a biomarker of oxidative stress) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 46 publications
3
37
0
Order By: Relevance
“…Another study of 2-NAP and 1-PYR reported associations with increases in malondialdehyde, another biomarker of oxidative lipid peroxidation. 35 Additionally, a study using biomarkers in urine collected at delivery observed significant positive association between 1-PYR and 8-OHdG. 36 NY in the placenta has been associated with particulate matter and other air pollutants, 37 but to our knowledge this is the first study of urinary biomarkers of PAH exposure and these outcomes in humans.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Another study of 2-NAP and 1-PYR reported associations with increases in malondialdehyde, another biomarker of oxidative lipid peroxidation. 35 Additionally, a study using biomarkers in urine collected at delivery observed significant positive association between 1-PYR and 8-OHdG. 36 NY in the placenta has been associated with particulate matter and other air pollutants, 37 but to our knowledge this is the first study of urinary biomarkers of PAH exposure and these outcomes in humans.…”
Section: Discussionmentioning
confidence: 86%
“…35, 4246 Urinary PAH metabolites reflect the internal dose from all recent exposure sources. Other studies of PAH exposure in pregnancy have examined PAH adducts in placenta, 47 indicative of the biologically effective dose in that tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Reported maternal fruit and vegetable consumption during pregnancy has been linked with increased fetal growth [47] as well as protective effects against the development of specific brain tumors [48] and the incidence of retinoblastoma [49] in childhood. More specifically related to protection against environmental exposures are studies indicating that consumption of fresh fruits and vegetables containing vitamin C during pregnancy appear to protect against oxidative stress associated with exposure to polycyclic aromatic hydrocarbons [50] and reduce the impact of air pollution on cognitive development in infants [51]. Nevertheless, when we attempted to adjust for dietary and SES factors in our multivariable models, there was no significant impact in nearly all instances.…”
Section: Discussionmentioning
confidence: 99%
“…We also found an increased fetal exposure to 1-hydroxypyrene, a known carcinogenic substance. The carcinogenic pathway for PAHs or their metabolites involves the production of reactive oxygen species, which generate oxidative stress, lipid peroxidation, protein modifications, and DNA damage, and may influence birth outcomes and child health in later life [46] , [47] , [48] , [49] .…”
Section: Discussionmentioning
confidence: 99%